KERUKUNAN BERLANDASKAN TRADISI DAN TOLERANSI KEBERAGAMAAN: PEMBELAJARAN DARI KOMUNITAS DESA PROBUR UTARA, NUSA TENGGARA TIMUR - Manan, M.Azzam (P2KK LIPI, 2018)
This article is a part and highlights of findings of research conducted in North Probur village, North-West Alor district of Alor region in 2017. It is written here to describe and proof that social harmony and unity in a traditional society is natural and running well without any disturbance even though their identity by languages and ethnics is quite different. From this study the fruitful lesson how unity develops social harmony in community life could be promoted and implemented both in local and national levels. In term of sociological perspective in which this study is addressed, this qualitative study found tradition and tolerance in religiosity or being religious as two prominent pillars the unity leading to social harmony within North Probur community possible. It means that the continuation of tradition in people’s daily life activities and the fact that religions that are divided into two mainstreams, Islam and Christianity, are embeded in their life and of course become indicators of their identity. In connection with sociological perspective, traditional culture as cultural capital in one hand and religions as social capital in the other hand are considered from their practices, ritual and institutional aspects in which social structure and social function of their formal and informal leaders are also quite important. All primary data related to research objective was information collected through field observation and in-depth interview with some relevant informants of those institutional officials, teachers and religiuos, cultural and youth leaders.